2015
DOI: 10.1590/01000683rbcs20150060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bioavailability of Heavy Metals After Vermicomposting in the Presence of Electronic Waste

Abstract: Heavy metals contained in electronic waste, if discarded improperly, can become bioavailable after vermicomposting, posing a risk to the environment. small-scale vermicomposting experiments were carried out with printed circuit boards (PCBs) to investigate the migration of heavy metals (Cu, Pb, Zn, Ni, and Sn) to the final compost, as well as the mobility and bioavailability of these metals. High total levels of Pb, sn and Cu in samples of manure with electronic waste (meW) and vegetables with electronic waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…In the residual fraction, (F 3 ) the order of association with the alumino-silicate minerals is: The results obtained in this study accord well with earlier research by Luo et al (2011), who found that Cd was associated with the exchangeable phase and Cu, Cr, Ni and Pb were predominantly associated with the residual fraction. Using a similar method to this study, Damasceno et al (2015) found Cu and Ni to be strongly associated with F 2 and F 3 , 67% Zn attributed to F 3 , and 92% Pb associated with F 2 . They suggested that the high levels of Pb in F 2 were a result of the complexation with humic substances formed by composting in presence of e-waste and Pb was the most bioavailable metal in their study.…”
Section: Chemical Speciation Of Metalssupporting
confidence: 54%
See 1 more Smart Citation
“…In the residual fraction, (F 3 ) the order of association with the alumino-silicate minerals is: The results obtained in this study accord well with earlier research by Luo et al (2011), who found that Cd was associated with the exchangeable phase and Cu, Cr, Ni and Pb were predominantly associated with the residual fraction. Using a similar method to this study, Damasceno et al (2015) found Cu and Ni to be strongly associated with F 2 and F 3 , 67% Zn attributed to F 3 , and 92% Pb associated with F 2 . They suggested that the high levels of Pb in F 2 were a result of the complexation with humic substances formed by composting in presence of e-waste and Pb was the most bioavailable metal in their study.…”
Section: Chemical Speciation Of Metalssupporting
confidence: 54%
“…The results in this study implies that Cd, closely followed by Sb, is potenitally the most bioavailable heavy metal, posing a risk to the environment as it is associated with the exchangeable fraction. Cr is least available for uptake, which corresponds with studies on E-waste sites by Luo et al (2011) and Damasceno et al (2015).…”
Section: Chemical Speciation Of Metalsmentioning
confidence: 59%
“…Metals in particular comprise approximately 60% of the weight of e‐waste (Vats & Singh, 2014), and tend to persist in the environment, thus posing potential risks to resident soil organisms (Masindi & Muedi, 2018). Damasceno et al (2015) have shown that e‐waste samples from printed circuit boards of obsolete computers can contaminate the environment with heavy metals. Earthworms are a particularly useful model organism to evaluate exposure to soil contaminants given that they have intimate contact with the soil and consume relatively large quantities (Parihar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Electronic waste is composed of a variety of metals such as copper, aluminum, iron, zinc, nickel, lead, cadmium and mercury, and is often deposited with various types of plastic and ceramic materials (Damasceno et al, 2015). Waste of electric and electronic equipment are often disposed with organic and household garbage being destined to landfills or dumps, what results in a process of compostaging of organic matter along with electronic residues.…”
Section: Discussionmentioning
confidence: 99%